Age-related gastrointestinal alterations of legumes and cereal grains digestibility. (June 2021) - Hernández-Olivas, Ever; Muñoz-Pina, Sara; Andrés, Ana; Heredia, Ana
Abstract: Aging is accompanied by changes in gastrointestinal functions. The impact of the gastrointestinal (GI) conditions of the elderly on the extent of proteolysis and glycolysis as well as calcium bioaccessibility in some cooked legumes (chickpea, lentils, soya bean and white bean) and cereals/pseudocereals (oats, spelt and quinoa) were studied. Samples were digested in vitro using three GI models specifically focused on the elderly in which oral, gastric and intestinal conditions were altered (E1: altered oral conditions, E2: altered oral and gastric conditions and E3: altered oral, gastric and intestinal conditions). Samples were also subjected to a standardized GI digestion as a control (C). The extent of proteolysis was only significantly affected with suboptimal intestinal conditions (p < 0.05). Protein digestibility of cereal grains decreased to a greater extent than for legumes. The release of non-essential amino acids was more affected than that of essential ones, mainly in legumes such as soya bean, lentils and white bean. The extent of glycolysis was much higher in cereal grains than legumes regardless of GI digestion conditions. Glycolysis declined with altered intestinal conditions (E3) compared to the C, in all legumes and spelt. Calcium bioaccessibility was much higher in cereal/pseudocereals than in legumes. However, calcium bioaccessibility seems to be highly limited in elderly people suffering from oral, gastric or intestinal alterations (up to 53% reduction compared to C). Such data might be helpful to develop dietary strategies based on protein-rich vegetal foods, including alternative crops such as oats, quinoa and spelt, specifically used to mitigate sarcopenia and osteoporosis in elderly people. Graphical abstract: Image 1 Highlights: GI conditions of the elderly lead to more proteolysis of legumes than cereal grains. The NEAA are more limited than EAA with the elderly. Extent of glycolysis was greater in cereals than legumes with the elderly GI conditions. Calcium release was highly influenced by the food matrix.